Comparative Study of Point Intercept Transect (PIT) Method and Underwater Photo Transect (UPT) to Calculate Hard Coral Cover Percentage - Johan Danu Prasetya; Dian Hudawan Santoso (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchPoint Intercept Transect Method (PIT) and Underwater Photo Transect (UPT) to monitor coral cover was comparedPercentage of hard coral cover was analyzedThe average difference of the percentage of hard coral cover obtained from the PIT and UPT was analyzed AbstractCoral reef ecosystems are vulnerable to damage and extinction. Therefore, it is imperative that, as part of conservation, their conditions are monitored using straight forward or easy-to-use methods. The research was intended to compare the effectiveness of using Point Intercept Transect (PIT) and Underwater Photo Transect (UPT) methods in calculating percent hard coral covers. It was conducted at six sites in Karimunjawa Islands, Indonesia: Cemara Besar, Cemara Kecil, Taka Malang, Tanjung Gelam, Menjangan Besar, and Menjangan Kecil. At each site, photographs of coral reefs were taken in two ranges of depths, shallow (3–6 m) and deep (9–12 m), along the length of the predefined transects (100 m for PIT and 50 m for UPT). In UPT, the photos were taken using a 58 x 44 cm frame. Fifty photo frames were collected then processed using Coral Point Count with Excel extensions (CPCe) 4.1. The results showed that PIT and UPT produced different percentages of hard coral cover at each site, with the most significant difference found in deep waters of Menjangan Besar (45.27%) and the least one in deep waters of Menjangan Kecil (0.08%). Overall, the difference in percent covers was averagely 9.79 percentage points, which is still categorized into small. Both methods have their own advantages and disadvantages. However, UPT is preferable because its results can be reanalyzed, especially the identified coral reef species.